Patient-Centered Data Home: A Path Towards National Interoperability - Williams, Karmen S.; Grannis, Shaun J. (Frontiers in Digital Health, 2022)
Objective: National interoperability is an agenda that has gained momentum in health care. Although several attempts to reach national interoperability, an interconnected network of Health Information Exchange (HIE) organizations has seen preliminary success. The aim was to characterize the Patient-Centered Data Home (PCDH) initiative through the Indiana Health Information Exchange’s participation in the Heartland Region Pilot. Materials and Methods: Admission, Discharge, and Transfer (ADT) transactions were collected between December 2016 and December 2017. ADTs were parsed and summarized. Overlap analyses and patient matching software were used to characterize the PCDH patients. R software and Microsoft Excel were used to populate descriptive statistics and visualization. Results: Approximately 1.5 million ADT transactions were captured. Majority of patients were female, ages 56-75 years, and were outpatient visits. Top noted reasons for visit were labs, screening, and abdominal pain. Based on the overlap analysis, Eastern Tennessee HIE was the only HIE with no duplicate service areas. An estimated 80 percent of the records were able to be matched with other records. Discussion: The high volume of exchange in the Heartland Region Pilot established that PCDH is practical and feasible to exchange data. PCDH has the posture to build better comprehensive medical histories and continuity of care in real-time. Conclusion: The value of the data gained extends beyond clinical practitioners to the public health workforce for improved interventions, increased surveillance, and greater awareness of gaps in health for needs assessments. This existing interconnection of HIEs has an opportunity to be a sustainable path towards national interoperability.